Analisis Faktor – Faktor Yang Mempengaruhi Produk Domestik Regional Bruto Pulau Jawa - Nanda Intania Permata Sari (Jurnal Ilmu Ekonomi, 2023)
This study aims to determine how the influence of the value of investment, labor, human development index, and government spending on Gross Regional Domestic Product in Java for the period 2012-2021. The method used in this study is regression analysis of panel data and supporting software from eviews 9. The results of the study conclude that investment, labor, and human development index simultaneously and partially have a positive and significant effect on the gross regional domestic product of districts in Java. Meanwhile, government spending has a negative and significant impact on the gross regional domestic product of districts in Java.   Penelitian ini bertujuan untuk mengetahui bagaimana pengaruh nilai investasi, tenaga kerja, indeks pembangunan manusia, dan pengeluaran pemerintah terhadap Produk Domestik Regional Bruto di Jawa periode 2012-2021. Metode yang digunakan dalam penelitian ini adalah analisis regresi data panel dan software pendukung dari eviews 9. Hasil penelitian menyimpulkan bahwa investasi, tenaga kerja, dan indeks pembangunan manusia secara simultan dan parsial berpengaruh positif dan signifikan terhadap produk domestik regional bruto. kabupaten di Jawa. Sementara itu, pengeluaran pemerintah berpengaruh negatif dan signifikan terhadap produk domestik regional bruto kabupaten/kota di Pulau Jawa.